Torque-velocity relation of pedaling movement against stepwise increase in load - Yamauchi, J.; Mishima, C.; Nakayama, S.; Ishii, N. (International Journal of Sport & Health Science, 2005)
Using a recumbent-type cycle ergometer, we investigated the validity of using a stepwise increment in load within a bout of exercise to determine the torque-velocity relation of pedaling movement. Fourteen healthy men and women performed pedaling exercise at their maximal effort on a recumbent-type cycle ergometer with an electromagnetic load control. Two types of loading were used: a conventional method (C) in which a varied load was applied to each bout independently; a "stepwise loading" method (S) in which the load was successively increased within a bout. In S, the external load was not applied initially, but when axial rotation velocity reached a maximum, it was increased in a stepwise manner until the velocity declined to 30% of the maximum. The torque-velocity relations obtained by both methods (C and S) were well described with linear functions and substantially identical, indicating that the present stepwise loading method is useful for a rapid evaluation of lower-limb muscle function.